2016
DOI: 10.1016/j.jiph.2015.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of human respiratory syncytial virus circulating in Iran

Abstract: Respiratory syncytial virus (RSV) is a leading cause of acute respiratory infection during early childhood and is associated with a great burden on patients, parents, and society. While no treatment is yet available, results from recent phase 2 clinical trials of cell-entry inhibitors and RSV vaccines are promising. To prepare for introduction of these novel therapeutics, good understanding of its molecular epidemiology and continuous RSV surveillance data are necessary. This paper provides an overview of RSV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
28
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 40 publications
(91 reference statements)
8
28
3
Order By: Relevance
“…We found in this review that the prevalence of HRSV infection was higher in children compared to adults. This is consistent with other reviews . Similar data were found in developed countries .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We found in this review that the prevalence of HRSV infection was higher in children compared to adults. This is consistent with other reviews . Similar data were found in developed countries .…”
Section: Discussionsupporting
confidence: 93%
“…A systematic review with meta‐analysis in China found a prevalence of 18.7% (95% CI 17.1‐20.5, 135 studies from 2010 to 2015) attributable to HRSV . Another systematic review with meta‐analysis of 21 studies (1996‐2013) in Iran yielded to a prevalence of 18.7% . Another meta‐analysis including participants with lower ARTI from Latin America found a prevalence varying from 40.9% among children aged less than 1 year to 12.6% adults aged more than 65 years .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These viruses are a significant cause of morbidity and mortality globally, especially among children in developing countries [1][2][3][4][5][6][7]. RSV is the most important pathogenic infection of childhood worldwide, causing a variety of manifestations from mild upper respiratory tract illnesses or otitis media to severe and potentially lifethreatening lower respiratory tract illnesses [6,[8][9][10][11]. Four PIV types (PIV1-4) have been identified [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…There are a few articles that investigate co-infection with important respiratory viruses such as RSV (23,24) in Iran. As, there is limited information on co-infection with coxsackievirus, HBoV and MP.…”
Section: Introductionmentioning
confidence: 99%